If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4xy + -2yx = 0 Combine like terms: 4xy + -2xy = 2xy 2xy = 0 Solving 2xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. xy = 0 Simplifying xy = 0 The solution to this equation could not be determined.
| 3(2x+8)=18 | | 8x+3=4x+43 | | 5-8=11+5 | | 4(x-6)=39-3x | | 9y+2z=24 | | 5+2x=1+3x | | 9y+2x=24 | | 2x+9y=24 | | -10x+15=30 | | x-3/2+x+9/3=3x+7/5+12 | | 16g^2+24g=9 | | (x+2)/(x+2) | | -27+(-31)= | | 5+2=37x | | 45+(-26)= | | 2*3+7= | | x+(2+x)+(4+x)=2(4+x) | | -40+58= | | -26+(-35)= | | 2x+5=2-x | | -36+(-56)= | | -36+(56)= | | 34+(-60)= | | 110=5x-5 | | 2j^2-7j=0 | | 0.06(8x-3)=0.48(x+7)-3 | | 6x+6=-90-6x | | 12=p+20 | | 97-3x=4x+134 | | 1.75= | | 15x+25=5x+175 | | 18x^3/6x |